A Novel Karyotype in Acute Myeloid Leukemia with Basophilia. (1st March 2014) - Servitzoglou, Marina; Grenzelia, Maria; Baka, Margarita; Harisi, Marietta; Pourtsidis, Apostolos; Bouhoutsou, Despina; Varvoutsi, Maria; Doganis, Dimitrios; Dana, Helen; Divane, Aspasia; Kosmidis, Helen
<x xml:space="preserve">Abstract</x> Acute basophilic leukemia is a distinct entity of Acute Myeloid Leukemia (AML) with primary differentiation to basophils. Increased basophil count has been described in AML cases with translocation t(6;9)(p23;q34) or other chromosomal abnormalities. We describe a 15-year old female teenager with AML and excess peripheral blood and bone marrow basophils. Her white blood cell count at diagnosis was 15.4 G/L with 53% basophils and 17% blasts. The bone marrow cytogenetics analysis did not reveal any of the usual abnormalities. The karyotype showed two closely related leukemic clones: the first (16 metaphases), with a total of 48 chromosomes, had an extra chromosome 8 with deletion of the long arm and an additional 21 (48, XX, +del(8)(q24.2q24.3), t21[16]), while the second clone (2 metaphases), with a total of 47 chromosomes, did not contain the extra 21 chromosome (47, sl, −21[2]). In summary, in this case of AML-M2 with excess basophils, there is a novel chromosomal abnormality, not previously reported in this entity.